CREBH Improves Diet-Induced Obesity, Insulin Resistance, and Metabolic Disturbances by FGF21-Dependent and FGF21-Independent Mechanisms - Aoi Satoh; Song-iee Han; Masaya Araki; Yoshimi Nakagawa; Hiroshi Ohno; Yuhei Mizunoe; Kae Kumagai; Yuki Murayama; Yoshinori Osaki; Hitoshi Iwasaki; Motohiro Sekiya; Morichika Konishi; et al. (iScience, 2020)
Summary: Mice overexpressing the nuclear form of CREBH mainly in the liver (CREBH-Tg) showed suppression of high-fat high-sucrose (HFHS) diet-induced obesity accompanied by an increase in plasma fibroblast growth factor 21 (FGF21) levels. CREBH overexpression induced browning in inguinal white adipose tissue (WAT) and whole-body energy expenditure, which was canceled in Fgf21−/− mice. Deficiency of FGF21 in CREBH-Tg mice mostly canceled the improvement of obesity, but the suppression of inflammation of epidermal WAT, amelioration of insulin resistance, and improvement of glucose metabolism still sustained. Kisspeptin 1 (Kiss1) was identified as a novel hormone target for CREBH to explain these FGF21-independent effects of CREBH. Knockdown of Kiss1 in HFHS-fed CREBH-Tg Fgf21−/− mice showed partially canceled improvement of glucose metabolism. Taken together, we propose that hepatic CREBH pleiotropically improves diet-induced obesity-mediated dysfunctions in peripheral tissues by improving systemic energy metabolism in FGF21-dependent and FGF21-independent mechanisms. : Obesity Medicine; Molecular Genetics Subject Areas: Obesity Medicine, Molecular Genetics